KEKUATAN ALAT BUKTI AKTA OTENTIK TERHADAP AKTA PEJABAT PEMBUAT AKTA TANAH (PPAT) BERDASARKAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 2016 JUNCTO PASAL 1868 KUHPERDATA - Abdul Wahid; Elya Kusuma Dewi; Sarip Sarip (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
The State of the Republic of Indonesia is a legal state (rechstaat) where the principle of state law is to ensure the certainty, order and protection of the law aimed at obtaining the truth and not being a state based on power (machtstaat) or where power is subject to law. The development of the law in the life of the society requires legal certainty on the legal relationship of individuals and subjects of law. Law is one of the means that everybody needs to fill their lives, especially in the economic system that enters the era of globalization. The need is manifested in the form of clear legal products and has legal certainty and strict law enforcement action of law enforcement officials. The public's need for legal products as a written evidence tool in a courtesy proof resulted in every public lawsuit involving the parties to be included in a letter of law. If a particular article is made so as to be a means of proof, then the letter or article is called the act is a special writing made to be written evidence. The act as a written evidence tool in certain cases is a powerful evidence tool for parties bound thereto. It is clear that the authentic deed in society is a widespread public need in civil law as regulated by the KUHPerdata, especially on the need for written proof.